The Role of Indonesian Dance as a Therapy Mediumin Nursing Homes in Europe - Nova Marseline (Journal of Aesthetics, Creativity and Art Management, 2026)
Each country has nursing homes and elderly care facilities with different standards of practice, adapted to various factors including climate, anatomy, and culture. The varying needs of nursing homes mean that routine activities are held within the homes to improve the quality of life of the residents. The challenge is how to introduce Indonesian dance to gain recognition and approval from the various agencies overseeing nursing homes in Europe, as a regular weekly program. This study used a qualitative approach, including interviews with sports therapists and elderly residents, observations of routine activities held in several nursing homes and elderly care facilities, and organizing and participating in small Indonesian-themed events, including dance performances and workshops, as a movement experiment for the elderly. In addition to its range of movements supporting respiratory function, Indonesian dance has high aesthetic value, carries specific meanings that can build the audience's psychological well-being, and can promote relaxation, especially for residents of nursing homes. Creating dance movements as therapy, based on various Indonesian dances, can help improve the quality of life for seniors through regular exercise through dance.